Do Enterprise Risk Management and Good Corporate Governance affect the Performance of Insurance Companies in ASEAN-5 Countries? - Cipto Hartono; Dewi Hanggraeni (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the influence of Enterprise Risk Management (ERM) and Good Corporate Governance (GCG) on the performance and profitability of companies among 30 insurance companies in the ASEAN-5 countries during the period of 2018-2022. The Panel Data Regression method is utilized to analyze data obtained from financial reports and corporate sustainability reports. The results of the analysis indicate that the simultaneous implementation of ERM and GCG does not have a significant positive influence on the financial performance of insurance companies, measured by indicators such as Return on Assets (ROA), Return on Equity (ROE), Loss Ratio, Combine Ratio, and Tobins Q. It is noteworthy that some individual parameters show a positive influence on company performance. This suggests that ERM and GCG play a crucial role in enhancing performance and profitability in the context of insurance companies in the ASEAN region during the research period.